What Is the Economic Impact of Infertility in Beef Cattle? - Chris Prevatt; Graham Cliff Lamb; Carl Dahlen; Vitor R.G. Mercadante; Kalyn Waters (EDIS)
Producers cannot completely control infertility in their cow herds. However, understanding and addressing the factors that affect infertility will help producers implement management practices that can improve fertility and reduce the negative impacts of infertility on the profitability of beef cow-calf operations. This 4-page fact sheet discusses reasons why beef cows fail to become pregnant or wean a calf, identification of infertile beef cows, and economic impacts of reduced fertility and infertility in beef cattle. Written by Chris Prevatt, G. Cliff Lamb, Carl Dahlen, Vitor R. G. Mercadante, and Kayln Waters, and published by the UF/IFAS Department of Animal Sciences, revised September 2018. https://edis.ifas.ufl.edu/an208